Fertilizer Recommendation: Correlation and Calibration Study of Soil P Test for Yard Long Bean (Vigna unguilata L.) on Ultisols in Nanggung-Bogor - Anas Dinurrohman Susila (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Yard long bean (Vigna unguilata L.) 777 was grown in Ultisols, which typically have low pH and high P-fixation, to determine the best correlation of soil extraction methods for soil P with yields, and to develop soil P response categories. The research was conducted at SANREM base camp in Hambaro Village, Nanggung, Bogor, Indonesia from April to August 2008. Treatments were arranged in a Split Plot Design with three replications. The main plots were treatments with soil P status of 0X, ¼X, ½X, ¾X and X, where is X = 1,590.5 kg SP-36 ha-1 (36% P2 O5 ) applied once a month before planting. The subplots were P application rate of 0, 75, 150, 225 and 300 kg P2 O5 ha-1. Yard long beans were planted in double rows per bed, 60 cm between rows and 25 cm within rows, 2 seeds per hole, with plot size of 1.5 m x 5 m. Coefficient correlation (r) of extraction reagents Olsen, Bray-1, HCl 25%, and Mechlich-1 were 0.772, 0.765, 0.755, and 0.732, respectively. Based on Olsen soil testing methods, soil response categories of very low, low, medium, and high were (ppm P2 O5 ) ≤ 18.40, 18.40 < P < 117.27, 117.27 < P < 267.04, and ≥ 267.04 extracted-P, respectively. Based on Bray-1 soil testing methods, soil response categories for low, medium, and high were ≤ 87.81, 87.81 < P < 233.78, and ≥ 233.78 extracted-P (ppm P2 O5 ), respectively. Fertilizer recommendation based on the Olsen soil test for low response category was 185.75 kg P2 O5 ha-1, and for the medium soil category was 175.97 kg P2 O5 ha-1. The Bray-1 soil test for the low response category was 184.31 kg P2 O5 ha-1 , and for the medium soil category was 161.39 kg P2 O5 ha-1 . Keywords: calibration, fertilizer recommendation, phosphorus, yard long bean